2007
DOI: 10.1504/ijtm.2007.013531
|View full text |Cite
|
Sign up to set email alerts
|

Achieving supply chain environment management: an exploratory study

Abstract: The concept of collaborating with supply chain parties to improve manufacturing sustainability is referred to as Supply Chain Environmental Management (SCEM) or 'greening the supply chain'. The extant literature suggests the benefits of SCEM but offers no guidelines for its development and practice. Using case research that involved direct observation and systematic interviews with five manufacturers, this study examines how manufacturing firms involve various supply chain partners (e.g. suppliers, customers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 49 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…Sarkis [151] conducts a multiple case study in a sample of 142 companies operating in South Korea to investigate the impact of energy-efficiency and environmental issues on logistics outsourcing. Yang and Sheu [152] carry out a case study highlighting how firms involve supply chain partners in their energy-efficient and sustainable processes.…”
Section: Ta4 Customer Perspective In Energy-efficient and Sustainablmentioning
confidence: 99%
“…Sarkis [151] conducts a multiple case study in a sample of 142 companies operating in South Korea to investigate the impact of energy-efficiency and environmental issues on logistics outsourcing. Yang and Sheu [152] carry out a case study highlighting how firms involve supply chain partners in their energy-efficient and sustainable processes.…”
Section: Ta4 Customer Perspective In Energy-efficient and Sustainablmentioning
confidence: 99%
“…Without trust, there can be no engagement in inter-firm information-sharing and joint collaboration. Some researchers [6,20,31,45,48] found that, when facing stressful and uncertain situations, the managers might develop distrust and fear toward their supply chain partners. If so, it is very possible that manufacturers, in the case of environmental uncertainty, are discouraged to rely on informal social ties to protect their interests.…”
Section: Discussionmentioning
confidence: 99%
“…These two governance mechanisms highlight the engagement of two informal supply chain activities during the implementation and fulfillment of a formal sustainability agreement. After the contract is signed, buyers and suppliers interact and cooperate with each other, with the intent of satisfying contract specifications and cooperating with unexpected contingencies, and such cooperation is referred to as problem-solving cooperation [6,19,28]. In general, problem-solving cooperation includes various activities, such as developing a standard approach to problem solving, establishing implicit agreements, and making a commitment to not alter facts to a party's advantage [28].…”
Section: Effects Of Relational Governancementioning
confidence: 99%
See 1 more Smart Citation
“…The report defines sustainable development as development that meets the needs without compromising the ability of future generations to satisfy their own needs. van Tulder, Kolk, and Van Wijk (2009) consider that organizations need to take the economic experience into account, but should also adopt wider social and environmental perspectives (Yang & Sheu, 2007). Potocan and Mulej (2003) made clear that the understanding of the sustainable development requires holism, professional, and political aspects in synergy, with systems thinking as a background for the creative and innovative society.…”
Section: The Challenge Of Sustainable Managementmentioning
confidence: 99%